2000
DOI: 10.1097/00007632-200002150-00015
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Intravascular Uptake in Lumbar Spinal Injection Procedures

Abstract: The incidence of intravascular uptake during lumbar spinal injection procedures is approximately 8.5%. The route of injection and the age of the patient greatly affect this rate. Absence of flashback of blood upon preinjection aspiration does not predict extravascular needle placement. Contrast-enhanced, fluoroscopic guidance is recommended when doing lumbar spinal injection procedures to prevent inadvertent intravascular uptake of injectate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
101
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 17 publications
5
101
1
2
Order By: Relevance
“…In a multicentre observational study investigating the incidence of intravascular uptake in lumbar spinal injection procedures, Sullivan et al reported that S1 transforaminal epidural steroid injection had the highest incidence of intravascular uptake at 19.9%, which was statistically significantly higher than transforaminal epidural steroid injection at the lumbar level [28]. They suggested that it was because the needle can potentially be positioned along the path of the vessel during S1 transforaminal epidural steroid injection in the anteroposterior view, especially when the needle is situated posterolaterally near the longitudinal vein (part of the posterior internal vertebral venous plexus) [28]. Considering the aforementioned vascular anatomy and Sullivan et al's explanation, we think that the procedure in the oblique view could reduce puncture risk to the posterior longitudinal vein and that the rate of intravascular uptake during S1 transforaminal epidural steroid injection in the oblique view may be as low as at the lumbar level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a multicentre observational study investigating the incidence of intravascular uptake in lumbar spinal injection procedures, Sullivan et al reported that S1 transforaminal epidural steroid injection had the highest incidence of intravascular uptake at 19.9%, which was statistically significantly higher than transforaminal epidural steroid injection at the lumbar level [28]. They suggested that it was because the needle can potentially be positioned along the path of the vessel during S1 transforaminal epidural steroid injection in the anteroposterior view, especially when the needle is situated posterolaterally near the longitudinal vein (part of the posterior internal vertebral venous plexus) [28]. Considering the aforementioned vascular anatomy and Sullivan et al's explanation, we think that the procedure in the oblique view could reduce puncture risk to the posterior longitudinal vein and that the rate of intravascular uptake during S1 transforaminal epidural steroid injection in the oblique view may be as low as at the lumbar level.…”
Section: Discussionmentioning
confidence: 99%
“…Both the posterior and anterior internal venous plexuses drain into the radicular veins, which accompany the radicular artery and spinal nerve through the intervertebral foramen [26,27]. In a multicentre observational study investigating the incidence of intravascular uptake in lumbar spinal injection procedures, Sullivan et al reported that S1 transforaminal epidural steroid injection had the highest incidence of intravascular uptake at 19.9%, which was statistically significantly higher than transforaminal epidural steroid injection at the lumbar level [28]. They suggested that it was because the needle can potentially be positioned along the path of the vessel during S1 transforaminal epidural steroid injection in the anteroposterior view, especially when the needle is situated posterolaterally near the longitudinal vein (part of the posterior internal vertebral venous plexus) [28].…”
Section: Discussionmentioning
confidence: 99%
“…[19,21] In the studies defining intravascular injection, it was not reported any complication after intravascular or intravenous contrast, steroid or local anesthetic injection. [20,21] Machikanti et al, [22] as a result of transforaminal epidural steroid injections at various levels in 100 patients, reported the rate of intravascular damage to be 16% in the lumbar region and 32% at the sacral level. Vascular penetration was observed in our 15 of 185 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Para gestantes poderia ser usada a ressonância magnética (57) . O uso de contraste também é importante para confirmar a posição da agulha dentro da articulação e para mostrar que não há absorção vascular do anestésico (fenômeno que resultaria em uma resposta falso-negativa) (69) . Idealmente, o bloqueio deve ser feito por alguém que não está tratando do paciente, a fim de evitar distorções.…”
Section: Discussionunclassified
“…In pregnant women MRI has been used (57) . The use of contrast is also important to confirm the needle position inside the joint and to show no vascular up take of the anesthetic (a phenomenon that would result in a false negative response) (69) . Ideally, the block should be performed by someone that is not treating the patient to avoid any bias.…”
Section: Discussionmentioning
confidence: 99%